2009
DOI: 10.2337/dc09-0132
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress at Work Doubles the Risk of Type 2 Diabetes in Middle-Aged Women

Abstract: OBJECTIVETo investigate the effect of psychosocial stress at work on risk of type 2 diabetes, adjusting for conventional risk factors, among a sample of British, white-collar, middle-aged men and women.RESEARCH DESIGN AND METHODSThis was a prospective analysis (1991–2004) from the Whitehall II cohort study. The current sample consists of 5,895 Caucasian middle-aged civil servants free from diabetes at baseline. Type 2 diabetes was ascertained by an oral glucose tolerance test supplemented by self-reports at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
177
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(200 citation statements)
references
References 22 publications
17
177
3
3
Order By: Relevance
“…Psychosocial stress [115] and effort-reward imbalance [116] are also being increasingly recognised as important risk factors for type 2 diabetes and need to be addressed specifically in future integrated interventions on diet, physical activity and lifestyle.…”
Section: Diabetes Prevention Beyond the Search For Optimal Dietary Apmentioning
confidence: 99%
“…Psychosocial stress [115] and effort-reward imbalance [116] are also being increasingly recognised as important risk factors for type 2 diabetes and need to be addressed specifically in future integrated interventions on diet, physical activity and lifestyle.…”
Section: Diabetes Prevention Beyond the Search For Optimal Dietary Apmentioning
confidence: 99%
“…Thus, low social support may be a stressor in itself with direct influences upon psychological symptomatology, irrespective of the presence of other stressful circumstances [31], which may potentially increase risk of type 2 diabetes [9]. A previous study using Whitehall II data found no association between social support at work and type 2 diabetes [13]. However, they used the iso-strain model, which includes four items on coworker support and supervisor support respectively, and define low social support as the lowest tertile.…”
Section: Discussionmentioning
confidence: 99%
“…the combination of high psychological demands at work and low job control, is a risk factor for type 2 diabetes [11]. In addition, a longitudinal study found that job strain was a risk factor for type 2 diabetes for women, and the association was stronger for women who also had low perceived social support at work [13]. Thus, social support at work may mitigate the effect of psychosocial stressors on risk of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now believed that, at any given severity, they face worse consequences than those with pre-existing diabetes [17]. Presumably protracted periods of stress and chronic cortisol production could conceivably produce hyperglycemia, increasing accumulation of body fat and enhancing insulin resistance [6]. This chronic stress condition may also lead not only to depression [4] but also to the development of impaired glucose tolerance and eventually overt T2DM and the associated complications such as dyslipidemia, stroke and hypertension [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that during periods of high metabolic demands, such as in the morning after an overnight fast, high cortisol levels ensue which leads to increased blood glucose via gluconeogenesis and glycogenolysis [2]. It is known that sustained hypercortisolemia, produced under a variety of stressful conditions, such as trauma and depression may promote insulin resistance and the associated complications [2]- [6]. Antidepressants and anxiolytic drugs may be used for the treatment and management of stress and they do show significant reduction in cortisol production and stress reactivity [2] [7].…”
Section: Introductionmentioning
confidence: 99%